Linguistic analysis of virtual course's terminology - Kaklauskienė, Danutė; Kaklauskas, Liudvikas (Lietuvos matematikos rinkinys, 2004)
A virtual course of computers architecture is analyses in the present article. A computer-aided set of words for this course is prepared. Results of frequentative analysis, according to methodologies of B. Davey and M. Bauman, show that analyzed text is of average complication. The analysis of usage of new terms shows that the text is not overloaded with unknown terms (only 3,455% of the whole set of words). On the ground of researches ofJ. Mikk and N.I. Gez we can state that the virtual course is not complicated as a student has to soak up 2.5 new terms during one academic hour. After carried out research, according to methodologies of W.S. Gray and B.E. Leary, we found out that too many long words and sentences are used, and this leads to difficulties when soaking up a new material. In summing up we can state that virtual course is of average complication.
Keywords: set of words; virtual course; term